The number «two» and dual concepts in Chinese linguoculturology (Journal of Oriental Studies, 2018)
This article analyzes the national-cultural aspect of the number «two» in the Chinese linguoculture bycomparative analysis in Kazakh language, as well as the national outlook and similarity in cultures of bothcountries. Also, some of the known linguistic scientists and Russian sinologists give their determinationsto the number «two». There are many examples of the number «two» concerning phraseological expressionsand equations related to the various etiquette units of the modern Chinese people’s ethnoculture.